Pengaruh Kualitas Pelayanan, Persepsi Kemudahan dan Keamanan Terhadap Kepuasan Peserta Dalam Menggunakan Jamsostek Mobile - Kadek Ferinda Devia Maharani; I Made Chandra Mandira (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to see the impact of service quality, perceived convenience, security partly and at the same time on participant satisfaction. The sample during this study was one hundred folks. the information analysis technique uses a validity take a look at, dependability take a look at, classical assumption take a look at, multiple statistical regression analysis determination on constant take a look at, f test, and t-test. From the results of the study, it had been found that service quality had a big positive impact on participant satisfaction, perceived convenience had a big positive impact on participant satisfaction, security had a big positive impact on participant satisfaction and repair quality, perceptions of convenience and security had a big positive impact on participant satisfaction. The magnitude of the influence of the freelance variables on participant satisfaction is fifty five.8. Suggestions which will incline by researchers ar BPJS Employment ought to still initiate on the offered options in order that Jamsostek Mobile will be accessed simply and is ready to supply quick responses, further as socialize the Jamsostek Mobile (JMO) application that is more practical, additionally to BPJS Employment Branch Bali Denpasar will add larva and admin applications to concentrate on handling social media in order that they will quickly reply to chat participants WHO wish to raise BPJS Employment data.